The Fashion Products Development Under The Perspective of Organizational Processes of Innovation: a case study in the premium fashion segment (ModaPalavra e-periódico, 2018)
This study aims to analyse the fashion products developing process, identifying their main activities and how they are distributed among the parts of the value chain. The classics theories of organizational processes of innovation presents adherent analogy to the product development processes in the fashion market since they organize them in activities and filters, selecting projects that must continue, be revised or cancelled, in order to generate a product portfolio, like a collection. Based on the theoretical framework, it was studied product development processes between a fashion factory and 64 of its clients, fashion brands. This analysis allowed us to understand the interdependence between these two links in the value chain and their main roles in the process of developing and selecting which products will be effectively marketed.
Keywords: product development; fashion business; innovation